Special properties of Fibonacci Array Based on Dimension - Jansirani, N; Subharani, V; Dare, VR (International Journal of Computer Sciences and Engineering, 2025)
In this paper the Fibonacci array based on the dimension are defined and analysed. The bordered width of the Fibonacci array is a Fibonacci number is shown. The concept of secondary transformation, linear tandem, diagonal tandem of an array are introduced. The combinatorial properties of the sub arrays are investigated. The Fibonacci array based on tree is represented and also Parikh vector concepts are discussed